Plagiat dzieł naukowych - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The subject of this study is the analysis of plagiarism of academic work in the light of binding legal regulations, in particular the Law of 4 February 1994 on copyright and related rights. It is worth stressing that the term ‘plagiarism’ is not a normative concept and it has not been applied by any Polish regulations on copyright. Although this term emerges in other legislative acts, for instance in Article 211, section 5, of the Law on higher education, and the Ordinance of the Ministry of Science and Higher Education of October 2011 on conducting studies in a given field and level of education. The term plagiarism arouses considerable reservations in legal doctrine, as does that of academic work, which is specific when compared to other kinds of work. Therefore, the paper presents various typologies of these terms. The term ‘plagiarism’ can be highly confusing because its meaning needs to be explained every time it is used. This is not to mean that such practice is admissible whatsoever. Therefore, the further part of the study discusses the consequences brought on by infringing copyright in terms of criminal, disciplinary, employee and civil law liability.